TWO NUCLEI TYPE IRIDIUM (I) PHOSPHINE COMPLEX AND USE THEREOF FOR CATALYST OF ASYMMETRIC HYDROAMINATION OF OLEFIN - EGLI PATRICK; DORTA ROMANO DR; TOGNI ANTONIO; BIELER NIKOLAUS; EYER MARTIN (1999)
PROBLEM TO BE SOLVED: To obtain the subject new compound consisting of an Ir (I) phosphine complex including cis/trans-isomers and their mixture, and capable of giving a high optical yield as an asymmetric hydroamination catalyst capable of being used by recycling many times. SOLUTION: This new iridium (I) phosphine complex is a new iridium (I) phosphine complex including cis/trans-isomers and their mixture expressed by formula I (X is fluorine, chlorine, bromine or iodine; formula II is in each case, a chiral bidentate diphosphine ligand), [e.g. ; (R)-2,2'-bis(diphenylphosphino)-1,1-binaphthalene], and useful as a catalyst keeping a high activity over many catalyst cycles and giving a high optical yield in an asymetric hydroamination. The complex compound is obtained by reacting a compound of formula III (coe is cyclooctene), etc., with a chiral and bidentate diphosphine in a nonpolar solvent.